Ketamine—From an Anesthetic to a Psychiatric Drug: Mechanisms of Action, Clinical Applications and Potential Risks - Ewa Gibuła-Tarłowska; Anna Wiszniewska; Magdalena Turyk; Paulina Szymczyk; Jolanta H. Kotlińska; Ewa Kędzierska (Molecules, 2025)
Ketamine, originally developed as an anesthetic, is gaining increasing attention due to its multifaceted pharmacological properties. In addition to its use in anesthesia, ketamine exerts potent analgesic effects via N-methyl-D-aspartate (NMDA) receptor antagonism, modulating pain perception and reducing central sensitization, particularly in chronic and neuropathic pain conditions. Emerging evidence also supports ketamine’s potential in the treatment of substance use disorder, where it may disrupt maladaptive reward-related memories and promote neuroplasticity which facilitates behavioral change. Moreover, in recent years, S-ketamine has shown rapid and potent antidepressant effects, especially in treatment-resistant depression (TRD), probably due to increased glutamatergic signaling, synaptic plasticity and the release of neurotrophic factors. This heterogeneous therapeutic profile positions ketamine as a unique agent at the interface of anesthesia, pain management, addiction medicine and psychiatry, warranting further exploration into its mechanism and long-term effectiveness.